Double Charge Transfer Dominates in Carrier Localization in Low Bandgap Sites of Heterogeneous Lead Halide Perovskites. (19th February 2021) - Fakharuddin, Azhar; Franckevičius, Marius; Devižis, Andrius; Gelžinis, Andrius; Chmeliov, Jevgenij; Heremans, Paul; Gulbinas, Vidmantas
Abstract: Heterogeneous organic‐inorganic halide perovskites possess inherent non‐uniformities in bandgap that are sometimes engineered and exploited on purpose, like in quasi‐2D perovskites. In these systems, charge carrier and excitation energy migration to lower‐bandgap sites are key processes governing luminescence. The question, which of them dominates in particular materials and under specific experimental conditions, still remains unanswered, especially when charge carriers comprise excitons. In this study transient absorption (TA) and transient photoluminescence (PL) techniques are combined to address the excited state dynamics in quasi‐2D and other heterogeneous perovskite structures in broad temperature range, from room temperature down to 15 K. The data provide clear evidence that charge carrier transfer rather than energy migration dominates in heterogeneous quasi‐2D perovskite films. Abstract : Temperature‐dependent transient absorption and time‐resolved photoluminescence investigations provide insights into electronic processes in heterogeneous organic‐inorganic halide perovskites. By taking 3D and quasi‐2D perovskite model systems, evidence is provided that charge carrier transfer (a double charge transfer) rather than energy migration dominates in heterogeneous quasi‐2D perovskite films.